The Structure of English Classroom Discourse in SMP Negeri 1 Tebing Tinggi - Eva Novelia Siregar; T. Silvana Sinar (LINGUISTIK TERAPAN, 2016)
This study is concerned with the structure of English classroom discourse in SMP Negeri 1 Tebing Tinggi. The objectives of this study were to describe the structures of English classroom discourse, to describe how the structures are linguistically realized and to reason for the realizations of the English class structure. The source of the data in this study was English teachers and also the students while the data are the utterances from the teacher and the students and semiotic markers as marked in the text. The instruments used for colleting data were video tape recorder and researcher’s fieldnote. The data were collected by observing and recording the utterances uttered by the teachers and students and writing all semiotics then classified them into types of exchanges as Sinclair and Coulthard theory. The research result mentioned that he structure of English classroom were teacher elicit, teacher direct, teacher information, boundary, pupil elicit, check, repeat, reinforce and reinitiating (II). These structures were dominantly realized by IR structure. English as a foreign language was also one point made the students afraid of uttering the utterances in teaching learning process.   Keywords: classroom discourse, pattern, Sinclair and Coulthard theory, structures.